Perioperative patient positioning following scalp tumor surgery: an anesthetic challenge - Rajnish Kumar; Nishant Sahay; Shagufta Naaz; Ansarul Haq; Rajesh Kumar (Ain Shams Journal of Anesthesiology, 2022)
Abstract Background Spindle cell tumors of the scalp are notorious for their potential to present with torrential life-threatening bleeds during surgery and in the postoperative period. We present the successful management of one such case. Case presentation A 54-year-old male was operated on for a huge spindle cell tumor of the scalp located in the occipital area. During surgery, blood loss of 2 l was replaced with crystalloids, colloids, and packed red cells. However, during the change of position from prone to supine immediately after surgery, the patient developed sudden and torrential bleeding from the surgical site, leading to asystole and cardiac arrest. The patient was revived and put on postoperative ventilatory support for 1 day in the intensive care unit. He could be discharged successfully without sequelae. Conclusions Positioning after surgery of a vascular tumor of the scalp should be gentle, slow, and monitored. Sudden movements predispose patients to secondary hemorrhage, which in scalp tumors could be torrential and life-threatening.